Wellbeing, independence and mobility: an introduction - Schwanen, T; Ziegler, F (Cambridge University Press, 2011)
This paper introduces the theme of the special issue on wellbeing, independence and mobility. We begin with outlining the complexity of each of these notions and then turn towards their interdependence. It is argued that the links between wellbeing, independence and mobility are manifold and contextual in older people's everyday lives: they differ between places, between individuals and across phases in each individual's unique lifecourse. The inherent complexity of those links can be examined fruitfully and understood better if a geographical or environmental analytical perspective is adopted. We also suggest that the interdependence of wellbeing, independence and mobility in later life needs to be understood in the context of neo-liberal governmentality and the creation of particular ways of being and acting for older people. The piece concludes with a brief description of the papers brought together in the special issue.